FORMULATION OF A CLEANSING BALM BASED ON VIRGIN COCONUT OIL USING RED DRAGON FRUIT PEEL (HYLOCEREUS POLYRHIZUS) EXTRACT AS AN ANTIOXIDANT - Sahrina, Erni; Elfiana, E; Suryani, S (Politeknik Negeri Lhokseumawe, 2025)
This study aimed to formulate a cleansing balm using natural active ingredients derived from red dragon fruit peel (Hylocereus polyrhizus, KBN) and virgin coconut oil (VCO). The treatments involved varying the ratios of virgin coconut oil (VCO) and red dragon fruit peel extract (Hylocereus polyrhizus, KBN) as well as mixing temperatures (60 °C, 65 °C, 70 °C, 75 °C, and 80 °C). Several quality parameters were evaluated, including organoleptic properties (color, fragrance, texture), antioxidant activity, homogeneity, pH, melting point, and cleansing efficacy. The total antioxidant content was determined using the DPPH assay and expressed as milligrams of vitamin C equivalent per gram of sample (mg VCE/g). The optimal formulation was obtained using 16% virgin coconut oil (VCO) and 9% red dragon fruit peel extract at a mixing temperature of 60 °C, yielding the highest antioxidant activity of 1.3486 mg VCE/g, a pH value within the recommended range for facial skin, and the highest organoleptic scores. These findings demonstrate that red dragon fruit peel is a promising source of natural bioactive compounds that can be effectively formulated into a safe and efficient cleansing balm product. Keywords: Antioxidant, Cleansing Balm, Maceration, Red Dragon Fruit Peel, Virgin Coconut Oil